Strategizing research and development investments in climate change adaptation for root, tuber and banana crops in the African Great Lakes Region: A spatial prioritisation and targeting framework - Vandamme, Elke; Manners, Rhys; Adewopo, Julius; Thiele, Graham; Friedmann, M.; Thornton, Philip K. (Elsevier, 2022)
CONTEXT Given the significance of climate change impacts on farming communities, large investments are made by research and development actors, including farmers themselves, to adapt agricultural systems. A data-driven approach is required to guide these investments and maximize their impact. In the African Great Lakes Region (GLR), root, tuber and banana (RT&B) crops are a vital component of smallholder farming systems, but little is known about strategies to mitigate climate change impacts on these crops.